TINGKAT PENGETAHUAN KESEHATAN REPRODUKSI PADA REMAJA - Yesa Ervina; Flauryta Indah Zahara (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
Adolescence is also called puberty, which is a unique transition period marked by various physical, emotional and psychological changes. During adolescence, you are very vulnerable to the negative influences of social media and the environment. Reproductive health is important for both men and women. The most prominent problems among teenagers today, for example, are sexual problems resulting in getting pregnant out of wedlock and then having abortions, then being vulnerable to infection with sexually transmitted diseases (STIs), HIV, AIDS and also drug abuse. It is hoped that this research can provide knowledge and insight into reproductive health problems and sexual deviations that they must avoid. Adolescents must be able to understand and know about sexual reproductive health so as not to produce sexual deviations that will harm themselves and their families.